2011
DOI: 10.1111/j.1744-7909.2011.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping of Dark‐Induced Senescence in Winter Wheat (Triticum aestivum)

Abstract: In order to explore the genetics of dark-induced senescence in winter wheat (Triticum aestivum L.), a quantitative trait loci (QTL) analysis was carried out in a doubled haploid population developed from a cross between the varieties Hanxuan 10 (HX) and Lumai 14 (LM). The senescence parameters chlorophyll content (Chl a+b, Chl a, and Chl b), original fluorescence (Fo), maximum fluorescence level (Fm), maximum photochemical efficiency (Fv/Fm), and ratio of variable fluorescence to original fluorescence (Fv/Fo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Comparative mapping shows this QTL to be close to our QTL for F v / F m QF v /F m .csdh - 2A identified near marker Xgwm339 by both CIM and SMA. In the same study, Li et al (2012) also located QTL on 6B and 7A ( QF v /F m .igdb - 7A ) which appear to be at the same chromosomal regions as our QTL QF v /F m .csdh - 6B.1 and - 6B.2 and QF v /F m .csdh - 7A.2 . A QTL associated with F v / F m at anthesis stage was detected by Liang et al (2010) on chromosome 6A close (about 10 cM difference) to the position of the QTL for F v / F m detected in our studies.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Comparative mapping shows this QTL to be close to our QTL for F v / F m QF v /F m .csdh - 2A identified near marker Xgwm339 by both CIM and SMA. In the same study, Li et al (2012) also located QTL on 6B and 7A ( QF v /F m .igdb - 7A ) which appear to be at the same chromosomal regions as our QTL QF v /F m .csdh - 6B.1 and - 6B.2 and QF v /F m .csdh - 7A.2 . A QTL associated with F v / F m at anthesis stage was detected by Liang et al (2010) on chromosome 6A close (about 10 cM difference) to the position of the QTL for F v / F m detected in our studies.…”
Section: Discussionsupporting
confidence: 83%
“…Although the genetic maps are not easy to compare, the QTL of Li et al (2012) appear to span the same region where our highly significant QTL for CF parameters, pigments and GWE were located. In contrast to these results, Zhang et al (2010) found no QTL for CF parameters on chromosome 6B.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations